The strange beauty and the beauty of the strange - Fonseca, Tania Galli Fonseca Galli (PORTO ARTE: Revista de Artes Visuais, 2019)
In this article, we seek to draw some observations on the career of the artist Luiz Gonzaga, from our reception to the exhibition of his works at the event Percurso do Artista, in 2014. We seek to associate life and work without worrying about collecting detailed and chronological biographical data, more like a biographeme, as Barthes tells us, since it is hardly possible for a man's biography to be fully apprehended. The path of the artist reveals itself as his creative and narrative drive, standing out as an expression of the failure of his achievements, since, even if he is satisfied with his last achievement, he finds himself compelled to tell once more, to seek in his anxieties answers that he knows will always be incomplete to the silences that populate him and the world. Thus, to tell an artist’s life would be to affirm this love to the strange by him nurtured and which ceases to be by becoming his own fuel.